WSÁNEĆ Legal Theory and the Fuel Spill at SELEK̵TEL̵ (Goldstream River) - Clifford, Robert (McGill Law Journal / Revue de droit de McGill, 2016)
SELEK̵TEL̵ (Goldstream River), on Coast Salish territory on Southern Vancouver Island in British Columbia, is an important salmon spawning river and fishing location for the WSÁNEĆ (Saanich) people. On April 16, 2011, it was also the site of a diesel and gasoline spill. In this article, I explore the processes of revitalizing WSÁNEĆ law and how we might think about the revitalization of WSÁNEĆ law in the context of this fuel spill. While I do not present a definitive statement of the application of WSÁNEĆ law, I explore what is needed in order to understand WSÁNEĆ law on its own terms. I turn to WSÁNEĆ stories to ground my understanding of WSÁNEĆ law in a different cosmological and ontological framework, and begin to explore the implications this different framework has for understanding the fuel spill and a WSÁNEĆ approach to “law”. I argue that this framework requires a greater attribution of “being” and “agency” to land, with an emphasis on repairing and maintaining relationships in an encompassing way. In exploring the implications of this shift in framework, I problematize the notions of “jurisdiction” and “remedy”. Specifically, rather than approaching the relationship to land through the idea of jurisdictional authority over it, I argue that WSÁNEĆ law develops a perspective centred on our mutual responsibilities with and to land. I also argue that the notion of jurisdiction can compartmentalize and limit WSÁNEĆ law’s attention to the encompassing nature of our relationships to land. Similarly, as opposed to engaging WSÁNEĆ law only to find a remedy, we must step back and consider how the harm of the fuel spill would be characterized within the distinctive framework of WSÁNEĆ law.